2019
DOI: 10.1038/s41598-019-46336-z
|View full text |Cite
|
Sign up to set email alerts
|

An Unusually Broad Series of Seven Cyclombandakamines, Bridged Dimeric Naphthylisoquinoline Alkaloids from the Congolese Liana Ancistrocladus ealaensis

Abstract: A series of seven unusual dimeric naphthylisoquinoline alkaloids was isolated from the leaves of the tropical liana Ancistrocladus ealaensis J. Léonard, named cyclombandakamine A (1), 1- epi -cyclombandakamine A (2), and cyclombandakamines A 3–7 (3–7). These alkaloids have a chemically thrilling structural array consisting of a twisted dihydrofuran-cyclohexenone-isochromene system. The 1′″-epimer of 4, cyclombandakamine A 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 28 publications
3
25
0
Order By: Relevance
“…The other northwestern molecular half consisted of a tetralone subunit linked to an isoquinoline part by a 5‴,8″-axis and by an oxygen bridge between C-1′′ and C-6′′′ (Figure 4A). NMR data evidencing such connections were identical to those already observed in the other, previously characterized cyclombandakamines, 11,13 among them joint HMBC correlations from H-7″, H-7‴, and H eq -4‴ to C-5″′, which indicated a 5′′′,8′′-coupling, and ROESY interactions between H-7′′ and both diastereotopic protons at C-4′′′ and between H-7′′′ and The connections between the two molecular halves, via the 6′,1″-axis and the C-2′′−O-5′−C-5′ oxygen bridge, to form an entire cyclombandakamine-type scaffold, were evident from HMBC cross-peaks between C-1′′ and both H b -3″ and H-6′ and from the chemical shift of C-2′′ (δ C 92.4) indicating it to be an acetal, together with ROESY interactions between CH 3 -3‴, in the northwestern isoquinoline portion, and H-7′, H-7, OCH 3 -8, and CH 3 -1 in the southeastern naphthylisoquinoline moiety (Figure 4A). Hence, the second isolated dimer, compound 8, was constitutionally different from its isomeric and co-occurring congener 3 only by its N-methyl pattern.…”
Section: ■ Results and Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…The other northwestern molecular half consisted of a tetralone subunit linked to an isoquinoline part by a 5‴,8″-axis and by an oxygen bridge between C-1′′ and C-6′′′ (Figure 4A). NMR data evidencing such connections were identical to those already observed in the other, previously characterized cyclombandakamines, 11,13 among them joint HMBC correlations from H-7″, H-7‴, and H eq -4‴ to C-5″′, which indicated a 5′′′,8′′-coupling, and ROESY interactions between H-7′′ and both diastereotopic protons at C-4′′′ and between H-7′′′ and The connections between the two molecular halves, via the 6′,1″-axis and the C-2′′−O-5′−C-5′ oxygen bridge, to form an entire cyclombandakamine-type scaffold, were evident from HMBC cross-peaks between C-1′′ and both H b -3″ and H-6′ and from the chemical shift of C-2′′ (δ C 92.4) indicating it to be an acetal, together with ROESY interactions between CH 3 -3‴, in the northwestern isoquinoline portion, and H-7′, H-7, OCH 3 -8, and CH 3 -1 in the southeastern naphthylisoquinoline moiety (Figure 4A). Hence, the second isolated dimer, compound 8, was constitutionally different from its isomeric and co-occurring congener 3 only by its N-methyl pattern.…”
Section: ■ Results and Discussionsupporting
confidence: 83%
“…The second new dimer, compound 8, was obtained as a yellowish amorphous solid, possessing the molecular formula C 49 H 53 N 2 O 8 (HRESIMS: m/z 797.380 95, [M + H] + ), which indicated that it was an isomer of the above-described spirombandakamine A 3 (7) and of the previously known and co-occurring dimers spirombandakamine A 2 (6) and cyclombandakamine A 1 (3). From its UV curve and from the observation of a 13 C NMR signal at δ C 196.2, which was reminiscent of the chemical shift of the carbonyl C atom of cyclombandakamines A 1 (3) and A 2 (4), 11 this metabolite was soon recognized to be a cyclombandakamine-type dimer.…”
Section: ■ Results and Discussionmentioning
confidence: 91%
See 3 more Smart Citations